Kharif onion production: An economic security for western rajasthan growers - Bhardwaj, R L; Parashar, Aabha (Indian Horticulture, 2023)
Onion (Allium cepa L.) is extremely important for its savour and spiciness as vegetable and spice crop not only for internal consumption but also as highest foreign exchange earner among the fresh agricultural produce. The country has three onion growing seasons, out of which kharif and late kharif season accounts for 40% of total onion production. The kharif production is highly vulnerable to erratic monsoon, cloudy weather, continuous drizzling which creates the problem of foliar as well as soil-borne diseases, but in western Rajasthan, all these problems are limited due to low rainfall and sandy soil condition. The produce of rabi season is stored for consumption in summer but due to non-congenial storage conditions and spoilage in the monsoon season, the availability of onion becomes less. Hence, production of onion during kharif is required for fulfilling the gap of consumers demand and stabilizing the prices of onion in our country.